2011
DOI: 10.1074/jbc.m111.276014
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Repression of the α7 Nicotinic Acetylcholine Receptor Subunit Gene (CHRNA7) by Activating Protein-2α (AP-2α)

Abstract: Background: Transcription of the ␣7 nicotinic receptor gene (CHRNA7) is decreased in schizophrenia. Results: Activating protein-2␣ (AP-2␣) is a potent repressor of CHRNA7 transcription. Conclusion: AP-2␣ may contribute to the decreased expression of the CHRNA7 gene in schizophrenia. Significance: This is the first report of a transcriptional repressor in the human CHRNA7 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…The present study provides the in vivo results showing that the SVadministration is able to elevate the levels of hippocampal α7nAChR mRNA and protein, but it did not affect the expression of hippocampal α4β2nAChR. A single promoter region on the upstream of transcription start site of α7nAChR subunit gene (CHRNA7) has been found to contain sequences for putative specificity protein family members, AP-2α, and early growth response factor [33]. We observed that the levels of hippocampal AP-2α mRNA and AP-2α protein in SV mice were lower than in control mice.…”
Section: Sv Administration Enhances Expression Of α7nachr Through Redmentioning
confidence: 63%
See 2 more Smart Citations
“…The present study provides the in vivo results showing that the SVadministration is able to elevate the levels of hippocampal α7nAChR mRNA and protein, but it did not affect the expression of hippocampal α4β2nAChR. A single promoter region on the upstream of transcription start site of α7nAChR subunit gene (CHRNA7) has been found to contain sequences for putative specificity protein family members, AP-2α, and early growth response factor [33]. We observed that the levels of hippocampal AP-2α mRNA and AP-2α protein in SV mice were lower than in control mice.…”
Section: Sv Administration Enhances Expression Of α7nachr Through Redmentioning
confidence: 63%
“…We observed that the levels of hippocampal AP-2α mRNA and AP-2α protein in SV mice were lower than in control mice. AP-2α has been reported to play a negative regulation in CHRNA7 transcription [33]. The supplement of isoprenoid FPP by applying FOH in SV mice could correct the decline of AP-2α level and block the increased expression of α7nAChR, whereas it did not alter the levels of AP-2α and α7nAChR expression in control mice.…”
Section: Sv Administration Enhances Expression Of α7nachr Through Redmentioning
confidence: 91%
See 1 more Smart Citation
“…The AP2-α gene has been identified as a potent repressor of CHRNA7 transcription (Finlay-Schultz et al, 2011). AP-2α is a transcription factor that binds in the proximal promoter of CHRNA7 .…”
Section: The Alpha7 Nicotinic Acetylcholine Receptor Gene Chrna7mentioning
confidence: 99%
“…For the other genes that we detect, Hek et al [43] reports that SNP rs161645 near NUDT12 is associated with depressive symptoms; NRN1L expresses predominantly in the nervous system [44] and may play a role in psychiatric diseases [45]; and STRA13 may have an effect on SCZ by influencing gene CHRNA7 [46].…”
Section: Real Data Applicationmentioning
confidence: 80%